Antibiotic Resistant Acinetobacter baumannii Isolated from Wounds Infections in Babylon Governorate - Zahraa A. Al-Ajeeli 1 , Habeeb S. Naher 2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This project has been carried out during a period of three months, September 2019 to November 2019. Onehundred swabs were collected from patients suffering from different wounds infections. Seven bacterialisolates have been identified as Acinetobacter baumannii using traditional diagnostic methods. Thesusceptibility of these isolates was determined towards seven antibiotics using disc diffusion test method.It was found that all isolates (100%) revealed remarkable resistance against Ampicillin and Cloxacillin,whereas the levels of resistance of those isolates were recorded at 71.4%, for each of Cefepime, clavulanicacid, kanamycin and gentamycin. The isolates exhibited a moderate susceptibility towards Amikacin whichaccounted for 57.1%. Azathromycin being more effective against Acinetobacter baumannii compared withother antibiotics included in this project since resistance of isolates accounted for only 14.2%.